Noble gas geochemistry - Ojima, Minoru (Cambridge University Press, 2002)
Noble Gas Geochemistry discusses the fundamental concepts of using noble gases to solve problems in the earth and planetary sciences. The discipline offers a powerful and unique tool in resolving problems such as the origin of the solar system, evolution of the planets, earth formation, mantle evolution and dynamics, atmospheric degassing and evolution, ocean circulation, dynamics of aquifer systems, and numerous applications to other geological problems. This book gives a comprehensive description of the physical chemistry and cosmochemistry of noble gases, before leading on to applications for problem-solving in the earth and planetary sciences. There have been many developments in the use of the noble gases since publication of the first edition of this book in 1983. This second edition has been fully revised and updated. The book will be invaluable to graduate students and researchers in the earth and planetary sciences who use noble gas geochemistry techniques.